Eccentricity Effects on the Efficiency of Attentional Networks: Evidence From a Modified Attention Network Test. (December 2016) - Wang, Bin; Zhao, Jingjing; Wu, Zheng; Shang, Wei; Xiang, Jie; Cao, Rui; Li, Haifang; Chen, Junjie; Zhang, Hui; Yan, Ting
The effects of eccentricity on the attentional modulation of visual discrimination have been widely studied; however, the substrate of this complex phenomenon is poorly understood. Here, we provided a measure of the effects of eccentricity on three attentional networks: alerting, orienting, and executive attention. Participants ( N = 63) were tested with a modified attention network test that included an additional eccentricity variation; this test allowed us to investigate the efficiency of the attentional networks at near and far eccentricities. Compared with targets at the near eccentricity, targets at the far eccentricity generally elicited significantly longer reaction times. We also found the far eccentricity was associated with smaller orienting effect scores and larger executive control scores than the near eccentricity. Interestingly, at the near eccentricity, executive control scores were larger when the spatial information was neutral (no cue, center cue, and double cue), but at the far eccentricity, the scores were larger when the spatial information was valid (spatial cue). We propose that the allocation of attentional resources differed among these cue conditions and influenced the interference caused by conflicting information.